The Photorespiratory BOU Gene Mutation Alters Sulfur Assimilation and Its Crosstalk With Carbon and Nitrogen Metabolism in Arabidopsis thaliana - Samuilov, Sladjana; Brilhaus, Dominik; Rademacher, Nadine; Flachbart, Samantha; Arab, Leila; Alfarraj, Saleh; Kuhnert, Franziska; Kopriva, Stanislav; Weber, Andreas P. M.; Mettler-Altmann, Tabea; Rennenberg, Heinz (Frontiers in Plant Science, 2018)
This study was aimed at elucidating the significance of photorespiratory serine (Ser) production for cysteine (Cys) biosynthesis. For this purpose, sulfur (S) metabolism and its crosstalk with nitrogen (N) and carbon (C) metabolism were analyzed in wildtype Arabidopsis and its photorespiratory bou-2 mutant with impaired glycine decarboxylase (GDC) activity. Foliar glycine and Ser contents were enhanced in the mutant at day and night. The high Ser levels in the mutant cannot be explained by transcript abundances of genes of the photorespiratory pathway or two alternative pathways of Ser biosynthesis. Despite enhanced foliar Ser, reduced GDC activity mediated decline in sulfur flux into major sulfur pools in the mutant, as a result of deregulation of genes of sulfur reduction and assimilation. Still, foliar Cys and glutathione contents in the mutant were enhanced. The use of Cys for methionine and glucosinolates synthesis was reduced in the mutant. Reduced GDC activity in the mutant downregulated Calvin Cycle and nitrogen assimilation genes, upregulated key enzymes of glycolysis and the tricarboxylic acid (TCA) pathway and modified accumulation of sugars and TCA intermediates. Thus, photorespiratory Ser production can be replaced by other metabolic Ser sources, but this replacement deregulates the cross-talk between S, N and C metabolism.